2020
DOI: 10.1029/2020gl089623
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Enhanced Levels of Peroxyacetyl Nitrate (PAN) During COVID‐19 in Beijing

Abstract: High levels of secondary air pollutants during COVID-19 in China have aroused great concern. In Beijing, measured daily mean peroxyacetyl nitrate (PAN) concentrations reached 4 ppb over the lockdown period (24 January to 15 February), whose averages were 2-3 times that before lockdown (1-23 January). The lockdown PAN levels also reached a high historical record based on our long-term measurements (2016-2019). Unlike ozone and PM 2.5 , PAN formation depends on less complex photochemistry between NO x and volati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…A variety of baseline inventories were used (Table 4), the most common being the global Emissions Database for Global Atmospheric Research (EDGAR) inventory (Crippa et al, 2020) and the Multi-resolution Emission Inventory for China (He, 2012). Many of the modeling studies adjusted their input emission inventories by scaling all emission sectors relative to changes in ambient or satellite observations (Griffith et al, 2020;Le et al, 2020a;Qiu et al, 2020;Zhang et al, 2020c;Zhang et al, 2021). Others have taken a sectorby-sector approach to scaling emission inventories (Forster et al, 2020;Le Quéré et al, 2020;Liu et al, 2020b;Menut et al, 2020;Yang et al, 2020) In general, by modeling both baseline and COVID-19perturbed emissions scenarios, the effects of meteorology can be isolated from those related to changes in emissions and can then be used to quantitatively assess the impacts of emission changes on the formation of secondary pollutants, such as O 3 and PM 2.5 .…”
Section: Air Quality Modeling and Emission Inventories Constrained Bymentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of baseline inventories were used (Table 4), the most common being the global Emissions Database for Global Atmospheric Research (EDGAR) inventory (Crippa et al, 2020) and the Multi-resolution Emission Inventory for China (He, 2012). Many of the modeling studies adjusted their input emission inventories by scaling all emission sectors relative to changes in ambient or satellite observations (Griffith et al, 2020;Le et al, 2020a;Qiu et al, 2020;Zhang et al, 2020c;Zhang et al, 2021). Others have taken a sectorby-sector approach to scaling emission inventories (Forster et al, 2020;Le Quéré et al, 2020;Liu et al, 2020b;Menut et al, 2020;Yang et al, 2020) In general, by modeling both baseline and COVID-19perturbed emissions scenarios, the effects of meteorology can be isolated from those related to changes in emissions and can then be used to quantitatively assess the impacts of emission changes on the formation of secondary pollutants, such as O 3 and PM 2.5 .…”
Section: Air Quality Modeling and Emission Inventories Constrained Bymentioning
confidence: 99%
“…, 2020),(Zhang et al, 2020d), United Kingdom:(Higham et al, 2020),(Fu et al, 2020;Zhang et al, 2020d), Russia:(Fu et al, 2020), Italy:(Fu et al, 2020), France:(Fu et al, 2020),(Zhang et al, 2020d), Spain:(Fu et al, 2020),(Martorell-Marugán et al, 2021),(Zhang et al, 2020d), and Germany:(Zhang et alet al, 2020a;Chen et al, 2020d;Jia et al, 2020b;Liu et al, 2020c;Qiu et al, 2020;Yuan et al, 2021), India:(Chatterjee et al, 2020;Panda et al, 2020), Italy:(Collivignarelli et al, 2020), United Kingdom: (Ropkins and Tate, 2020), Canada: (Adams, 2020), United States:(Xiang et al, 2020), and Brazil:(Nakada and Urban, 2020;Siciliano et al, 2020b) AOD India:(Gautam, 2020b;Ranjan et al, 2020;Zhang et al, 2020d), China(Diamond and Wood, 2020;Ghahremanloo et al, 2020;Zhang et al, 2020d;Shen et al, 2021), South Korea, and Japan(Ghahremanloo et al, 2020), North America, and Europe(Zhang et al, 2020d) NMVOCs China:(Ghahremanloo et al, 2020;Jia et al, 2020b;Qiu et al, 2020), South Korea:(Ghahremanloo et al, 2020), Japan:(Ghahremanloo et al, 2020;Zhang et al, 2020b), India:(Beig et al, 20...…”
mentioning
confidence: 99%
“… 1 , 7 , 8 , 17 22 Studies also confirmed that the enhanced formation of secondary aerosols under adverse meteorological condition contributed to the severe haze event. 1 , 8 , 20 , 23 However, most existing studies focused on the influence of emission reduction, meteorological condition, or holiday effect on gaseous pollutants and main inorganic compositions of PM 2.5 , only a few explored organic aerosol (OA) which contributed to 42% of PM 2.5 in Beijing during the Spring Festival of 2020. 1 …”
Section: Introductionmentioning
confidence: 99%
“…Compared with the relatively low concentration of O3 in autumn and winter seasons (Wang et al, 2013), PAN pollution events are also observed in cold days over the NCP (Zhang et al, 2014;Liu et al, 2018;Zhang et al, 2019;Zhang et al, 2020a;Qiu et al, 2019b; associated with particulate pollution events. For example, Qiu et al (2020b) reported a high PAN level of 4.13 ppb during the COVID-19 lockdown period of January-February 2020 in Beijing, and the average value was 52% higher than that in summer 2019 when solar radiation was intensive. A common explanation for the observed high PAN concentration in winter is its susceptibility to be accumulated under a stable atmosphere and regional transport due to decreased thermal decomposition under low temperatures (Qiu et al, 2019b;Zhang et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…A common explanation for the observed high PAN concentration in winter is its susceptibility to be accumulated under a stable atmosphere and regional transport due to decreased thermal decomposition under low temperatures (Qiu et al, 2019b;Zhang et al, 2020a). In addition, accelerated photochemistry can also play a role during PAN pollution events in cold days (Zhang et al, 2014;Liu et al, 2018;Qiu et al, 2020b;Zhang et al, 2020a) since unexpectedly high PAN concentrations are usually observed during the daytime. Thus, PAN could represent a key indicator of photochemistry in cold seasons.…”
Section: Introductionmentioning
confidence: 99%